INTEGRATING ISLAMIC VALUES INTO ENGLISH MATERIALS - Andi Asmawati; Ahmad Riadi (Univeristas Islam Negeri (UIN) Alauddin Makassar, 2022)
This study aims to determine students’ needs in learning materials by integrating Islamic values into English. This study used quantitative method. The participants were eighth-grade students, consisting of 29 students. This study employed a close-ended questionnaire divided into three sections: organization of the learning material, learning content, and learners' characteristics. Data were analyzed using quantitative data analysis techniques. The results indicated that there are three characteristics of the students' needs. They were the organization materials, the content materials, and learners’ characteristics. In the organization materials, most of the students needed the instructional objectives in English learning materials. Regarding the content materials, the students wanted the virtue of studying, helping parents, and environment as learning topics by integrating them with Islamic values. For the learners’ learning characteristics, they preferred the visual learning style.